Response of human pulps capped with different self-etch adhesive systems - Accorinte, M. L. R.; Loguercio, A. D.; Reis, A.; Costa, Carlos Alberto de Souza [UNESP] (Springer Heidelberg, 2008)
The aim of this study was to evaluate the response of human pulps capped with a calcium hydroxide hard-setting cement or with two-step self-etch adhesive systems. Pulp exposures were performed on the occlusal floor, and the bleeding control was performed with saline solution. The exposed pulp tissue was capped with Clearfil LB 2V (2V) or Clearfil SE Bond (SE) and restored with a composite resin. In control group, the pulpal wound was capped with Ca(OH)(2) cement and restored with Clearfil LB 2V or Clearfil SE Bond + composite resin. After 30 and 90 days, the teeth were extracted, processed for hematoxylin and eosin, and categorized in a histological score system. The pulpal response was worse for groups capped with the self-etch adhesive systems (2V and SE) in both periods of evaluation, when compared to their respective control groups at 90 days (p < 0.05). For both self-etch systems evaluated, the pulp tissue exhibited moderate to severe inflammatory cell infiltrate involving the coronal pulp with chronic abscesses. Dentin bridging was observed in a few specimens. For the calcium hydroxide groups, almost all specimens showed dentin bridge formation, with few scattered inflammatory cells and normal tissue below the pulp exposure site. Calcium hydroxide should be used as the material of choice for pulp capping, and the use of two-step self-etch adhesives for human pulp capping is contraindicated.
Keywords: pulp exposure; self-etch adhesive systems; pulpal response